Rose of Jericho - Grecian, Alex (2025)
"Something wicked is going on in the village of Ascension. A mother wasting away from cancer is suddenly up and about. A boy trampled by a milk cart walks away from the accident. A hanged man can still speak, broken neck and all. The dead are not dying. When Rabbit and Sadie Grace accompany their friend Rose to Ascension to help take care of her ailing cousin, they immediately notice that their new house, Bethany Hall, is occupied by dozens of ghosts. And something is waiting for them in the attic. The villagers of Ascension are unwelcoming and wary of their weird visitors. As the three women attempt to find out what's happening in the town, they must be careful not to be found out. But a much larger--and more dangerous--force is galloping straight for them." -- Publisher annotation.